Penerapan Project-Based Learning Pada Pembelajaran Tematik Terpadu Untuk Meningkatkan Hasil Belajar Siswa Kelas V Sekolah Dasar - Putri, Cindy Hendrica; S, Farida (Universitas Negeri Padang, 2024)
This research is motivated by the lack of application of new and creative ways of learning. Sometimes, when a group of people work together on this learning, they don’t work as well as they could. This study uses qualitative and quantitative research in the form of classroom action research (CAR). It was carried out in two cycles covering four stages, namely preparation, implementation, observation and reflection. Researchers as practitioners, class teachers as observers, and fifth-grade students at SDN 01 Pauh Padang City were the subjects of this study. The research findings revealed an increase: the observation of lesson plans in cycle I received a Good qualification (B) increased in cycle II to obtain a Very Good qualification (SB), the movement of educators in cycle I received a Enough qualification (C) increased in cycle II to obtain a Very Good qualification (SB), the actions of students in cycle I got the qualification Enough (C) increased in cycle II to get the qualification Very Good (SB), and student learning outcomes in cycle I got a score with the qualification Enough (C) increased in cycle II got an average score of Good ( B). Based on the research findings, it can be concluded that integrated thematic learning with the Project Based Learning model can improve the learning outcomes of fifth-grade elementary school students.